Asuhan Kebidanan Ibu Hamil, Bersalin, Nifas Dan Bayi Baru Lahir Normal Pada Ny “J” Dengan G3P1A1 - Sainah (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
The purpose of this study was to analyze in depth the pattern of Midwifery Care for Pregnant, Maternity, Postpartum and Normal Newborns in Mrs. "J" with G3P1A1 in the work area of ​​RSU Bahagia Makassar. Research Methods: This type of research is descriptive analytic through cross sectional in the form of a case study to explore the problem of Midwifery Care in Pregnant Women, Maternity, Postpartum and Normal Newborns in NY "J" at Happy General Hospital Makassar. Midwifery care was carried out on Date March 24, 2022 to April 03, 2022. Results: After analyzing and interpreting the data, the gestational age was 37 weeks 0 days, 38 weeks 0 days, with the results of ANC I to ANC II proceeding normally. For 2 times ANC never felt excessive complaints. The diagnosis obtained was G3P1A1 Pregnant 38 weeks 4 days with active phase I inpartu, live single fetus with cephalic presentation. Mrs. "J"'s labor duration from stage I to stage IV, namely the first stage lasted 5 hours, the second stage 15 minutes, the third stage 5 minutes, and the fourth stage lasted 2 hours, proceeded normally with no complications. Research implications The results of the ANC, first stage of labor, second stage, second stage, fourth stage did not have complications, while the puerperium did not have bleeding and infection. In newborns the first 6 hours the baby is healthy, cries loudly, and starts looking for and sucking the nipple. From the objective data, weight 2600 grams, PB 49 cm, there were no complications in the baby.